ANALISIS PRODUKSI TEMBAKAU RAJANGAN TIPE MUNTILANAN DALAM POLA KEMITRAAN CV. MERABU - PT. DJARUM KUDUS - Sumartono, Eko (Jurnal AGRISEP, 2016)
The aims of this research are to analyse the factors influenced production of tobacco and  to count the tobacco productivity.  This research  applies a descriptive method and multiple regression analysis. Result of research indicates that level of input usage, production rate and level of productivity, quality of tobacco type Muntilanan has experienced a drastic degradation from the year 2005 to 2009. Hereinafter level of input usage experiences upsurge, although some inputs still experience a degradation. Number of partnership member, seed, NPK Fertil/Basal, Ortheen/Roteen 75 SP, Marcis, Hylan/ Suckericide Prime Plus, years of 2006, years of 2007, years of 2008 and years of 2009 are significant factors affecting production while number of partnership member,Seed, NPK Fertil/Basal, KNO3, Hylan/ Suckericide Prime Plus, Marcis, Year of 2006, and Year of 2009 are important factors to affect productivity.